En bloc excision and customized prosthesis replacement for Campanacci III giant cell tumours of the distal radius: five cases report and a review of the literature - Ningjun Wan; Zhen Wang; Shaowei Xu; Bin Hao (BMC Musculoskeletal Disorders, 2025)
Abstract Background Giant cell tumours of the distal radius are highly aggressive local bone tumours. En bloc resection of Campanacci grade III giant cell tumours of the distal radius has been promoted as a reliable method for achieving local control, associated with the dual problem of bone defect reconstruction and functional recovery. Through a case report and a literature review, we evaluated the local recurrence, clinical effect, and complications of prosthesis replacement for treating Campanacci III giant cell tumours of the distal radius. Methods 5 patients with Campanacci III giant cell tumours of the distal radius received en bloc excision and customized prosthesis replacement from February 2016 to December 2021 in our department. Oncology efficacy, wrist range of motion, MSTS scores, and surgical complications were evaluated during follow-up. Grip strength was measured using a hydraulic hand dynamometer. Results Five patients were followed up for 5 to 38 months, with an average follow-up time of 18.40 ± 13.69 months. No local tumour recurrence or lung metastasis occurred by the date of the last follow-up. Functional results revealed that the average active ROM of the wrist was 38.6° (range 30°-45°) of dorsiflexion, 40.8° (range 25°-47°) of volar flexion, 31.2° (range 24°-40°) of supination, 22.2° (range 16°-30°) of pronation, 13.8° (range 10–16°) of radial deviation, 14.8° (range 12°-18°) of ulnar deviation, and mean grip strength was 59% (50-76%). The overall revised MSTS score averaged 73.8% (63-83%). One patient experienced a superficial infection one week after surgery, and the incision healed after an intravenous infusion of antibiotics. During the follow-up period, there was no wrist dislocation or prosthesis loosening. Conclusion En bloc resection of Campanacci grade III giant cell tumours of the distal radius may reduce the local recurrence rate, and a prosthesis reconstruction is still an alternative option.